2009
DOI: 10.1007/s00018-009-0187-z
|View full text |Cite
|
Sign up to set email alerts
|

The p38/MAPK pathway regulates microtubule polymerization through phosphorylation of MAP4 and Op18 in hypoxic cells

Abstract: In both cardiomyocytes and HeLa cells, hypoxia (1% O(2)) quickly leads to microtubule disruption, but little is known about how microtubule dynamics change during the early stages of hypoxia. We demonstrate that microtubule associated protein 4 (MAP4) phosphorylation increases while oncoprotein 18/stathmin (Op18) phosphorylation decreases after hypoxia, but their protein levels do not change. p38/MAPK activity increases quickly after hypoxia concomitant with MAP4 phosphorylation, and the activated p38/MAPK sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(117 citation statements)
references
References 49 publications
(51 reference statements)
6
111
0
Order By: Relevance
“…It is known that Hypoxia treatment could reduce cell viability (Hu et al, 2010). We found that S82A improved the survival of hypoxic cells whereas S82E sharply reduced cell viability in hypoxia conditions.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…It is known that Hypoxia treatment could reduce cell viability (Hu et al, 2010). We found that S82A improved the survival of hypoxic cells whereas S82E sharply reduced cell viability in hypoxia conditions.…”
Section: Discussionmentioning
confidence: 60%
“…This process is critical for the apical delivery of membrane cargoes and S82 phosphorylation leads to a reduced affinity for the dynein intermediate chain (Yeh et al, 2006). Since the above mentioned reports indicated a key role of DYNLT1 in modulating mPT and MT network stability, we hypothesized that phosphorylation of DYNLT1, especially on S82, might occur in hypoxia, based on our previous work in which we showed that hypoxia-activated p38/MAPK signaling pathway initiates MT disruption and alters cell viability by phosphorylating the downstream effector (Hu et al, 2010). In order to generalize these observations, we chose H9c2 and HeLa cells (Brito and Rieder, 2009;Wan et al, 2009) to study hypoxiareduced MTs disruption and mitochondrial permeabilization related to S82.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…4 Also in the MAPK cascade, apoptosis signal-regulating kinase (ASK1) activates the JNK and p38 MAPK cascades through STNM1 phosphorylation and ASK1 is involved in a broad range of activities including cell differentiation and stress-induced apoptosis. [45][46][47][48] Moreover, ribosomal protein S6 kinase A3 (RPS6KA3, RSK2) can reduce microtubule depolymerization by phosphorylation of STMN1 specifically at Ser16 residue. 49 Additionally, peptide hormones as gonadotropin--releasing hormone (LHRH) secreted from hypothalamic neurons, regulators of LH and FSH synthesis and release, have also been described to induce STMN1 phosphorylation in a PKC-dependent pathway.…”
Section: Stmn1 and Cell Migrationmentioning
confidence: 99%
“…Zhang et al also found that p38/MAPK involved in burn-induced degradation of myocardial cell membrane phospholipids, and revealed that it achieved such effects by adjusting cytosolic phospholipase A2 (cPLA2) (Zhang et al, 2007b). Moreover, hypoxia was recently found to cause myocardial cell microtubule depolymerization through activation of p38/MAPK and change of phosphorylation level of microtubule associated protein 4 (MAP4) and oncoprotein 18/stathmin (Op18) (Hu et al, 2009). Additionally, through F-actin cytoskeleton rearrangement and phosphorylation of L-caldesmon, p38/MAPK conducted an important role in endothelial barrier dysfunction induced by burn serum (Chu et al, 2010).…”
Section: Mechanism For Cardiac Damage / Heart Function Depression At mentioning
confidence: 99%